Legal Frameworks and Land Acquisition: A Study of Infrastructure Development in Decentralized Manokwari - Ullo, Epidika; Watofa, Yohana; Bernhard, Jefry (Legalis : Journal of Law Review, 2024)
This research discusses land acquisition to promote infrastructure in Manokwari, West Papua Province. Infrastructure development in this city, as the capital of the province, has significant challenges related to land acquisition, dispute resolution, legal protection, community participation, and project sustainability. Civil law plays a crucial role in regulating these aspects, which include land acquisition regulations, civil conflict resolution, protection of individual rights, and public participation. The research used a qualitative approach to analyze primary and secondary data, including interviews and Focus Group Discussions (Focus Group Discussion  (FGDS), to identify challenges and solutions in civil law implementation. The results show that while there is a clear legal framework, effective implementation requires improved coordination, transparency, and public participation to ensure sustainable infrastructure development that benefits the people of Manokwari.